2016
DOI: 10.1142/s021812741650098x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Chaotic Flow with a Plane of Equilibria

Abstract: Using a systematic computer search, a simple four-dimensional chaotic flow was found that has the unusual feature of having a plane of equilibria. Such a system belongs to a newly introduced category of chaotic systems with hidden attractors that are important and potentially problematic in engineering applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(43 citation statements)
references
References 27 publications
(20 reference statements)
0
41
0
2
Order By: Relevance
“…Quite recently, chaotic mathematical models with multiple line equilibrium have been proposed. One such example can be found in report 47 and can be described in general form (2) together with the following functions:…”
Section: System With Line Equilibriummentioning
confidence: 99%
See 3 more Smart Citations
“…Quite recently, chaotic mathematical models with multiple line equilibrium have been proposed. One such example can be found in report 47 and can be described in general form (2) together with the following functions:…”
Section: System With Line Equilibriummentioning
confidence: 99%
“…Both the cases are provided in Ref. 47 and a comprehensive study of another di®erent \hyperbolic" case can be found in Ref. 48.…”
Section: Model With Hyperbolic and Parabolic Equilibriummentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there has been an increasing effort in constructing new chaotic attractors with pre-designed types of equilibria [1][2][3][4][5][6][7][8][9][10][11][12]. These systems include dynamical systems with no equilibrium points [13][14][15][16][17][18][19][20][21], with only stable equilibria [22][23][24][25][26][27], with curves of equilibria [28][29][30], with surfaces of equilibria [8,9], and with non-hyperbolic equilibria [31,32].…”
Section: Introductionmentioning
confidence: 99%